The nature, portrayal of eternity and economic use of Non-birdsong subjects in La Rousserolle Effarvatte, from Catalogue d’Oiseaux by Oliver Messiaen - Loo, Fung Chiat; Loo, Fung Ying (Universidade Federal de Goias, 2025)
.This paper examines the longest work from Catalogue d’oiseaux, La rousserolle effarvatte, focusing on the non-birdsong subjects that depict the nature and habitat of the solo birdsong, the reed warbler. The analysis reveals that Messiaen used the time of day and non-birdsong subjects to structure the work, incorporating elements such as pond music, sunrise and sunset, and flower themes. It also shows that many of the non-birdsong subjects employ Messiaen’s harmonic language, including résonance contractée, thème d’accords, and others, to represent these subjects. Many of the harmonic progressions used in this work appear in previous compositions such as Le Merle Noir (1952), Turangalîla-Symphonie (1946-48), and Cantéyodjayâ (1949), indicating Messiaen’s economical use of material, which may also explain the significance of his compositions.